SISTEM INFORMASI PENERIMAAN MAHASISWA BARU BERBASIS WEB (Studi Kasus: Sekolah Tinggi Teknologi Ronggolawe Cepu) - Bella Rizky; Joko Handoyo (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2016)
Admission of new students (PMB) is an activity of the new candidate selection was held each year on the basis of the value of thetest results and rapot to be accepted in college. Information system web-based admissions this particular online registration can be onealternative implementation activities of the admission of new students in a high school Technology Ronggolawe.The research method used was the development of the system, namely experiments for designing information systems Web basedadmissions. Ronggolawe. This software development method also uses a System Development Life Cycle (SDLC) with a waterfall modelconsisting of the planning phase of the system, analysis, design, coding, testing, and maintenance. Testing instruments done through testfunctionality and black box testing. Admissions information system using Codeigniter as a Framework.Resolve the matter, a single information system Web-based Admissions which will make it easier for the Committee in the processdata registries on the admissions process, thus generating the quickly information, easily and accurately. The result of test functionality ofthe admission information system stated worth in therm of functionality, with 100% result on black box testing of suitability characteristicsand accurancy.